Matricide and schizophrenia- psychopathological, psychodynamic, and forensic aspects: a case report - Valença, Alexandre Martins; de Almeida, Letícia Rodrigues; de Oliveira, Gustavo Carvalho; França, Milena Ferreira; da Silva, Antônio Geraldo; Telles, Lisieux Borba; Nardi, Antonio Egidio (Frontiers in Psychiatry, 2023)
Matricide is the murder of a mother by her son or daughter, a form of homicide rarely seen in psychiatric practice. A narrative review was conducted on the relationship between matricide and schizophrenia, followed by a case report in Brazil of a schizophrenic patient who murdered his mother and was submitted to forensic psychiatric assessment for criminal liability. The article discusses psychopathological, psychodynamic, and forensic aspects related to the case. The observation of ambivalent and conflictive relations between schizophrenic individuals and their mothers suggests the need for family-level interventions to resolve the understandable occurrence of emotional conflicts, which can serve as stimuli that trigger the murder.